Wei Weng, Hew: Chinese Ways of Being Muslim: Negotiating Ethnicity and Religiosity in Indonesia (2018). NIAS Press. Copenhagen. xxvi + 305 pp. [NIAS Monographs 140]. ISBN 978-87-7694-211-3. Price £ 22.50 (Paperback) - Seise, Claudia (Azizah) (IIUM Press, International Islamic University Malaysia, 2019)
Chinese Ways of Being Muslim: Negotiating Ethnicity and Religiosity in Indonesia poses a welcoming contribution to the intersection of Chinese and Muslim identity in Indonesia. Both identity expressions were restricted during the New Order regime and have experienced a revival since its end in 1998. Much has been written on the re-discovery of Chineseness, even more so on the different forms of Islamic revival in Indonesia. However, as the author rightly identified, the (inter)- connection between the two has been neglected. Wei Weng shows in his book that Chinese and Muslim identity in Indonesia have more in common than it might appear at first sight. Both, Muslim and Chinese identities, had been surpressed. Expressions of Islam, as well as expressions of Chineseness, were restricted. In addition, both identites are multiple and fluid. There is no single Chinese or Islamic identity in Indonesia. The official national motto of Indonesia Bhinneka Tunggal Eka (Unity in Diversity) is present everywhere. Looking further into the similarities of Chinese and Muslim identities, Wei Weng finds that Chineseness and Islamicness are probably the two most commodified and visible identities in Indonesia’s markets today. Here, Rudnycsky’s Market Islam comes to mind, and how Muslim religious ethics are designed to merge with capitalism and consumer culture. Furthermore, both identities carry a transnational dimension, connected to the Chinese diaspora and the Muslim ummah. Wei Weng uses ‘Islamic ummah’, which I find problematic because the ummah is made up of Muslims, meaning people. However, ‘Islamic’ implies the notion of ideology, which is problematic when refering to a community as diverse as the Muslim ummah. To unite the two identities, the author argues that